2019
DOI: 10.3390/fi11060136
|View full text |Cite
|
Sign up to set email alerts
|

Developing Internet Online Procurement Frameworks for Construction Firms

Abstract: Electronic purchasing or e-procurement saves millions of dollars yearly in transaction costs. E-procurement helps to cut down the supplier base, promotes paperless transactions, and increases transparency and accountability in the procurement process. Nonetheless, studies report that around 80% of e-procurement initiatives have met with failure and failed to achieve the desired results. Although studies to better understand the Critical Success Factors (CSFs) of e-procurement implementation involving various i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 39 publications
0
11
0
Order By: Relevance
“…Analogous to the driving indicators of EP and the related critical success factors, studies including [89][90][91] also examined the underlying factors that contribute to the successful adoption and implementation of EP. The factors were captured under two primary frameworks: (1) implementation success framework for project management success and (2) user satisfaction.…”
Section: Ep Implementation: Boosters and Barriersmentioning
confidence: 99%
“…Analogous to the driving indicators of EP and the related critical success factors, studies including [89][90][91] also examined the underlying factors that contribute to the successful adoption and implementation of EP. The factors were captured under two primary frameworks: (1) implementation success framework for project management success and (2) user satisfaction.…”
Section: Ep Implementation: Boosters and Barriersmentioning
confidence: 99%
“…Step 5-Eligibility As mentioned above, the 151 publications were subjected to a more in-depth study and analysis using more rigorous inclusion/ exclusion criteria to select publications that qualified for the final sample as follows: 1) publications were required to primarily focus and contribute to DT in the construction sector, including the project, organizational, and industry levels of construction operation [e.g., Bonanomi et al 's (2019) study on the impact of DT on the organizational structures in large AEC firms]; 2) publications were required to use DT as the theoretical lens of research and may use this theoretical lens: propose hypotheses; identify the research variables; for data collection; for explaining research findings; and to drawing conclusions and recommendations; and 3) publications that are neither 1) nor 2) were excluded; such publications are more practitionercentered offering insights on the implementation of digital technologies to relevant stakeholders [e.g., Deraman et al, 2019;Soman and Whyte, 2020;Zima et al, 2020]. The eligibility process resulted in a final sample of 36 journal publications that met the criteria.…”
Section: Step 3-selection Of Abstractmentioning
confidence: 99%
“…Also, digital technologies can be very disruptive. The process-centric strategic consideration allows an incremental implementation of digital technologies, which helps control the rate of diffusion of implemented technology before reaching the disruptive stage (Deraman et al, 2019;Morgan, 2019).…”
Section: Processmentioning
confidence: 99%
“…Cardoso and Biazzin [17] considered the benefits of e-procurement to maintenance, repairs and operations suppliers. In Deraman et al [18] developed an electronic purchasing (e-procurement) framework for construction also indicating that these systems have sometimes failed. According to [18], procurement policy, employee commitment, project milestones, change management, stakeholder involvement and project planning influence the decision to implement an eprocurement framework in the construction industry.…”
Section: Review Of Related Literaturementioning
confidence: 99%
“…In Deraman et al [18] developed an electronic purchasing (e-procurement) framework for construction also indicating that these systems have sometimes failed. According to [18], procurement policy, employee commitment, project milestones, change management, stakeholder involvement and project planning influence the decision to implement an eprocurement framework in the construction industry. Amade et al [19] indicated that the most important factors for successful supply chain management was relationship among supply chain partners, supply chain financing and supply chain and continuous performance measurements.…”
Section: Review Of Related Literaturementioning
confidence: 99%